New generalized the Hermite-Hadamard inequality and related integral inequalities involving Katugampola type fractional integrals - Almutairi, Ohud; Kilicman, Adem (Multidisciplinary Digital Publishing Institute, 2020)
In this paper, a new identity for the generalized fractional integral is defined. Using this identity we studied a new integral inequality for functions whose first derivatives in absolute value are convex. The new generalized Hermite-Hadamard inequality for generalized convex function on fractal sets involving Katugampola type fractional integral is established. This fractional integral generalizes Riemann-Liouville and Hadamard’s integral, which possess a symmetric property. We derive trapezoid and mid-point type inequalities connected to this generalized Hermite-Hadamard inequality.